Berlitz Indonesian CD pack (Singapore Berlitz/APA, 2006)
This CD contains eight topics to help in learning Indonesian, starting from basic Indonesian expressions, and includes more than 300 useful words and phrases. The phrasebook contains more than 1,200 words and phrases and an easy-to-understand pronunciation guide.
"Indonesian travel pack"--Container.
Compact disc.
In English and Indonesian.
Keywords: Indonesian language -- Self-instruction.; Indonesian language -- Conversation and phrase books -- English; Indonesian language -- Spoken Indonesian